PENGARUH STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI: STUDI KASUS BANK NAGARI CABANG SITEBA - Ria Triyanti; Zusmawati Zusmawati (LP2M Universitas Bina Bangsa, 2024)
The purpose of this research is to test the influence of work stress variables on employee performance (Case Study of Bank Nagari Siteba Branch), to test the influence of job satisfaction variables on employee performance (Case Study of Bank Nagari Siteba Branch). Data were collected through distributing questionnaires to 40 respondents using saturated sampling techniques, where all members of the population were sampled, using validity tests, reliability tests, descriptive analysis, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression and t tests with the help of SPSS application. The results of the research show that work stress has a positive and significant effect on employee performance (Case Study of Bank Nagari Siteba Branch), job satisfaction has a positive and significant effect on employee performance (Case Study of Bank Nagari Siteba Branch)